Methamphetamine and HIV-1 gp120 Effects on Lipopolysaccharide Stimulated Matrix Metalloproteinase-9 Production by Human Monocyte-Derived Macrophages - Reynolds, Jessica L. (2011)
Monocytes/macrophages are a primary source of human immunodeficiency virus (HIV-1) in the central nervous system (CNS). Macrophages infected with HIV-1 produce a plethora of factors, including matrix metalloproteinase-9 (MMP-9) that may contribute to the development of HIV-1-associated neurocognitive disorders (HAND). MMP-9 plays a pivotal role in the turnover of the extracellular matrix (ECM) and functions to remodel cellular architecture. We have investigated the role of methamphetamine and HIV-1 gp120 in the regulation of lipopolysaccaride (LPS) induced-MMP-9 production in monocyte-derived macrophages (MDM). Here, we show that LPS-induced MMP-9 gene expression and protein secretion are potentiated by incubation with methamphetamine alone and gp120 alone. Further, concomitant incubation with gp120 and methamphetamine potentiated LPS-induced MMP-9 expression and biological activity in MDM. Collectively methamphetamine and gp120 effects on MMPs may modulate remodeling of the extracellular environment enhancing migration of monocytes/macrophages to the CNS.